If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (t + -8)(t + -5) = 0 Reorder the terms: (-8 + t)(t + -5) = 0 Reorder the terms: (-8 + t)(-5 + t) = 0 Multiply (-8 + t) * (-5 + t) (-8(-5 + t) + t(-5 + t)) = 0 ((-5 * -8 + t * -8) + t(-5 + t)) = 0 ((40 + -8t) + t(-5 + t)) = 0 (40 + -8t + (-5 * t + t * t)) = 0 (40 + -8t + (-5t + t2)) = 0 Combine like terms: -8t + -5t = -13t (40 + -13t + t2) = 0 Solving 40 + -13t + t2 = 0 Solving for variable 't'. Factor a trinomial. (5 + -1t)(8 + -1t) = 0Subproblem 1
Set the factor '(5 + -1t)' equal to zero and attempt to solve: Simplifying 5 + -1t = 0 Solving 5 + -1t = 0 Move all terms containing t to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -1t = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -1t = 0 + -5 -1t = 0 + -5 Combine like terms: 0 + -5 = -5 -1t = -5 Divide each side by '-1'. t = 5 Simplifying t = 5Subproblem 2
Set the factor '(8 + -1t)' equal to zero and attempt to solve: Simplifying 8 + -1t = 0 Solving 8 + -1t = 0 Move all terms containing t to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + -1t = 0 + -8 Combine like terms: 8 + -8 = 0 0 + -1t = 0 + -8 -1t = 0 + -8 Combine like terms: 0 + -8 = -8 -1t = -8 Divide each side by '-1'. t = 8 Simplifying t = 8Solution
t = {5, 8}
| 7x+6-3x=13x+17 | | x-4.3=19 | | -1-2=3y | | -54=-4(3n+1)+2n | | (7v+3)(7v+9)=0 | | y=-2x^5+16x^4+66x^3 | | z^2-5z+7+z=0 | | 15z^2+7z-16=0 | | g(9g+7)=0 | | 8x+8=38 | | x+8.8=33 | | .80x+.85(40)=.40(75) | | (f-8)(8f-5)=0 | | 7x+3-2x+9-5x=19 | | (1+2i)(1-2i)=0 | | 2.25=-2.67x-1.83x | | 8a+11=3a+41 | | x+7.7=33 | | (r-8)(r+1)=0 | | x-25=-65 | | 6(r-4)=-5r+31 | | y=10x^4-360x^2 | | (k-8)(k+2)=0 | | x^2+bx+c=r | | v+5.5=31.1 | | 4.3t-2.1t-0.2c=7.6 | | 3(4x+7)=9x-3 | | 5z-23=-41+3z | | (z+7)(4z+9)=0 | | 8x-30+6x+84=180 | | 4(3x+2)-3= | | 1.3+v=5.3 |